Mendorong Aktualisasi Remaja Dalam Berorganisasi Dan Memupuk Jiwa Kepemimpinan - Lorita, Evi; Kader, Bando Amin C.; Juwita, Juwita; Putri, Rusvika (LPPJPHKI Universitas Dehasen Bengkulu, 2022)
This Community Service Program aims to encourage student actualization in school organizations and foster leadership skills among students of SMK Negeri 4 Kota Bengkulu. Using presentations and discussions, students were educated about the essential role of school organizations, particularly OSIS, in shaping character, management abilities, and relevant soft skills. The program was conducted on May 30, 2023, involving 45 participants. The results indicated an increase in student motivation to actively participate in organizations, enhanced self-confidence, and awareness of leadership grounded in responsibility and solidarity. This activity is expected to contribute significantly to improving student quality and serves as a collaborative effort between higher and secondary education in shaping capable and socially responsible youth.